Palmitoylethanolamide counteracts brain fog improving depressive‐like behaviour in obese mice: Possible role of synaptic plasticity and neurogenesis. (3rd June 2020) - Lama, Adriano; Pirozzi, Claudio; Annunziata, Chiara; Morgese, Maria Grazia; Senzacqua, Martina; Severi, Ilenia; Calignano, Antonio; Trabace, Luigia; Giordano, Antonio; Meli, Rosaria; Mattace Raso, Giuseppina
Abstract : Background and Purpose: High‐fat diet (HFD)‐induced obesity is accompanied by metabolic and neurochemical changes that have been associated with depression. Recent studies indicate that palmitoylethanolamide (PEA) exerts metabolic effects and holds neuroprotective potential. However, studies on HFD exposure in mice which investigate the effects of PEA on monoamine system and synaptic plasticity are limited. Experimental Approach: In C57Bl/6J male mice, obesity was established by HFD feeding for 12 weeks. Then, mice were treated with ultra‐micronized PEA (30 mg·kg −1 daily p.o.) or vehicle for 7 weeks along with HFD. Mice receiving chow diet and vehicle served as controls. Thereafter, depressive‐, anhedonic‐like behaviour and cognitive performance were measured. Monoamine analyses were performed on brain areas (nucleus accumbens, Nac; prefrontal cortex, PFC; hippocampus), and markers of synaptic plasticity and neurogenesis were evaluated in hippocampus. Key Results: PEA limited depressive‐ and anhedonic‐like behaviour, and cognitive deficits induced by HFD. PEA induced an increase in 5‐HT levels in PFC, and a reduction of dopamine and 5‐HT turnover in Nac and PFC, respectively. Moreover, PEA increased dopamine levels in the hippocampus and PFC. At a molecular level, PEA restored brain‐derived neurotrophic factor signalling pathway in hippocampus and PFC, indicating an improvement of synaptic plasticity. In particular, PEA counteracted the reduction of glutamatergic synaptic density induced by HFD in the stratum radiatum of the CA1 of the hippocampus, where it also exhibited neurogenesis‐promoting abilities. Conclusion and Implications: PEA may represent an adjuvant therapy to limit depressive‐like behaviours and memory deficit, affecting monoamine homeostasis, synaptic plasticity and neurogenesis. LINKED ARTICLES: This article is part of a themed issue on Neurochemistry in Japan. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.4/issuetoc Abstract :